Technology Innovation Project. Establishment of farmer field school for the Introduction of alley cropping systems to improve soil management and productivity of crops in the Toledo district of Belize - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
This document contains information about the project Establishment of farmer field school for the Introduction of alley cropping systems to improve soil management and productivity of crops in the Toledo district of Belize which have the object To improve soil management and productivity of corn through the establishment of alley cropping systems in the Toledo district, Belize